2022
DOI: 10.7717/peerj.13168
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of differential anther development from sterile/fertile lines in Capsicum annuum L.

Abstract: Background Pepper (Capsicum annuum L.) is a major cash crop throughout the world. Male sterility is an important characteristic in crop species that leads to a failure to produce functional pollen, and it has crucial roles in agricultural breeding and the utilization of heterosis. Objectives In this study, we identified many crucial factors and important components in metabolic pathways in anther and pollen development, and elucidated the molecular mechanism related to pollen abortion in pepper. Methods Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…In the previous proteomic studies of pepper, 1645 differentially abundant proteins were found via proteomic analysis, 45 of which were related to the anther and pollen development of MS lines of pepper, indicating that many proteins were involved in the flowering process of pepper ( Pei et al., 2022 ). Mutations in different strains can result from various factors, including natural environmental influences or external environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous proteomic studies of pepper, 1645 differentially abundant proteins were found via proteomic analysis, 45 of which were related to the anther and pollen development of MS lines of pepper, indicating that many proteins were involved in the flowering process of pepper ( Pei et al., 2022 ). Mutations in different strains can result from various factors, including natural environmental influences or external environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In WA352 , the rice chorionic felt layer can be triggered prematurely by PCD, leading to pollen abortion [ 56 ]. Premature or delayed PCD of the chorionic felt layer in Arabidopsis all led to the occurrence of male sterility [ 57 ]. Similarly, some studies have reported that the adenine phosphoribosyl transferase activity deficient mutants in Arabidopsis were male sterile, which could be attributed to the abortion of pollen [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serially diluted commercial recombinant PA (rPA, 171E, List Labs, Campbell, CA, USA) was the reference standard. To identify the constituents of the CSE vaccine, the culture supernatant from starting strain A16R and the CSE vaccine were identified using tandem mass tags (TMT, A44522, Thermo Fisher Scientific, MA, USA) and liquid chromatography-tandem mass spectrometry (LC-MS/MS, EASY-nLC 1200 UPLC system, Thermo Fisher Scientific) as previously described [ 21 ]. The differentially expressed proteins (DEPs) were considered upregulated if |FC (A16R/CSE)| ≥ 1.2 or downregulated if |FC (A16R/CSE)| ≤ 0.83 with corrected P -values < 0.05.…”
Section: Methodsmentioning
confidence: 99%